Implementasi Peraturan Daerah Kota Palangka Raya Nomor 11 Tahun 2017 Tentang Rencana Induk Pembangunan Kepariwisataan Kota Palangka Raya Tahun 2017-2028 - Rhama, Bhayu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Palangka Raya, 2022)
This study aims to find out and examine the implementation of the development of tourism in the city of Palangka Raya and also to find out what the benefits of tourism development for the community.The author uses the theories of Donald Van Metter and Carl Van Horn which are influenced by six indicators, namely the Size and Objectives of Policies, Resources, Characteristics of Implementing Agents, Attitudes / Dispositions of Implementers, Communication between Organizations and Implementing Activities, and Economic, Social and Environmental Political. This study used qualitative research methods. Data taken based on information from informants at the element level of the Head of Tourism, Attractiveness Management Section in the City Culture and Tourism Office of Palangka Raya and the Community and data obtained through the results of field research. Data announcement techniques in the form of observations and interviews.The results showed that the Culture and Tourism Office had implemented Palangka Raya City Regulation No. 11 of 2017 concerning the Master Plan for the Development of Tourism in Palangka Raya 2017-2028 quite well. Given that this development is a long-term nature, the government prioritizes development at several points that have the highest tourism potential, but the Culture and Tourism Office still lacks Human Resources with a tourism background to improve their performance. The benefits of tourism development felt by the people of Palangka Raya city are seen from several aspects, namely economic aspects, social and cultural aspects, environmental aspects, aspects of social values and science as well as aspects of opportunities and employment opportunities.